Does Shariah Supervisory Board Moderate the Effect of Islamicity Performance Index and Intellectual Capital on Financial Performance? - Salsabila, Zahrah; Widyastuti, Shinta (KnE Social Sciences, 2024)
This research aims to analyze the effect of Islamicity Performance Index and intellectual capital on financial performance in Islamic banks moderated by Shariah supervisory board. The research used 168 sample data from 36 companies consisting of Sharia Bank (BUS) and Sharia enterprise unit (UUS) registered by Otoritas Jasa Keuangan in 2018-2022. The analysis technique used is multiple linear regression analysis with STATA version 17, as a tool. The result concluded profit sharing ratio, zakat performance ratio, Islamic income vs non-Islamic income ratio, and intellectual capital do not affect financial performance. Meanwhile, an equitable distribution ratio has a positive effect on financial performance. The Sharia supervisory board does not strengthen the effects of the profit sharing ratio, zakat performance ratio, and Islamic income vs non-Islamic income ratio. However, the Shariah supervisory board strengthens the effect of equitable distribution ratio and intellectual capital on financial performance. The research contributes to developing new insight into the recent phenomena and the novelty of variables. Research limitations are only using 4 of the 7 Islamicity Performance Index proxies, the object is only in the Indonesian region, and the literature on Sharia supervisory boards is limited. Keywords: financial performance, intellectual capital, Islamic banking, Islamicity Performace Index, Sharia supervisory board